Inhibitory effect of norharmane on Serratia marcescens NJ01 quorum sensing-mediated virulence factors and biofilm formation. Issue 2 (24th February 2021) - Luo, Huai-Zhi; Zhou, Jin-Wei; Sun, Bing; Jiang, Huan; Tang, Shi; Jia, Ai-Qun
Abstract: Serratia marcescens NJ01, a Gram-negative bacterium, can infect tomato leaves and cause chlorosis and wilting. The present study evaluated the quorum sensing (QS) and biofilm inhibitory effects of seven carboline compounds against S. marcescens NJ01 at 20 μg ml −1, and subsequently focused the study on norharmane as this had the best inhibitory activity. Quantitative real-time polymerase chain reaction (qRT-PCR) analysis confirmed the down-regulation of QS and biofilm related genes bsmA, bsmB, fimA, fimC, flhD, pigA, pigC and shlA on exposure to norharmane. Fourier-Transform Infrared Spectroscopy (FT-IR) analysis showed a reduction in the major components of the exopolysaccharide (EPS) matrix such as nucleic acids, proteins and fatty acids, which are involved in forming the tertiary structure of biofilms. Norharmane exposure also enhanced the susceptibility of the biofilm to ofloxacin. Hence, norharmane has the potential for use as an antibiotic adjuvant to enhance the efficacy of conventional antibiotics to reduce pathogenic bacterial infections.